Mainstreaming Pesantren and Madrasah - Burhanudin, Jajat; Jabali, Fuad (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2007)
PPIM UIN Syarif Hidayatullah, Jakarta, assisted by PUSKADIA-BUMA UIN Sunan Kalijaga, Yogyakarta has conducted a three year project (2004-2007) of mainstreaming pesantrens and madrasahs in Indonesia. The project initiative and execution were the result of cooperation between UIN Jakarta and the Royal Danish Embassy The project was intended to introduce contemporary, democratic civic values (democracy, civil society, religious pluralism, human rights, and gender equality) into pesantrens and madrasahs and to their leaders, and to initiate participatory and accountable management within these schools. The program was designed to eventually create an atmosphere in which the worldviews of Islamic educational institutions could change and adapt to the diversity and complexity of the modern world.DOI: 10.15408/sdi.v14i3.553